PENGARUH SERVICE QUALITY, PERCEIVED VALUE, TRUST, CUSTOMER SATISFACTION TERHADAP LOYALTY DI PATUNA TOUR & TRAVEL - Prabowo, Arif; Mardhiyah, Dien (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2023)
This study examines the effect of service quality, perceived value, trust, and customer satisfaction on loyalty in Patuna Tour & Travel. The data analysis technique used in this study uses a partial least square. The sample used was 360 individual respondents or ex-pilgrims who had, at least twice, used the services of Patuna Tour & Travel in carrying out the Umrah pilgrimage. The results showed that service quality has a positive effect on perceived value, service quality has a positive effect on customer satisfaction, service quality has a positive effect on trust, perceived value has a positive effect on customer satisfaction, perceived value has a positive effect on trust, customer satisfaction has a positive effect on trust, trust has a positive effect positive on loyalty and customer satisfaction does not affect loyalty